HEALTH BELIEF APPLICATION MODEL: KNOWLEDGE AND PATTERNS OF IRON SOURCE FOOD CONSUMPTION AS A PREVENTIVE EFFORT FOR ANEMIA EVENTS - Stefani Verona Indi Andani; Trias Mahmudiono; Yurike Dhika Adhela (Universitas Airlangga, 2021)
ABSTRACT Female adolescents are prone to iron deficiency anemia due to regular menstrual cycles and loss of basal, thus requiring sufficient iron intake from food consumed daily. The concept of the Health Belief Model which consists of perceived susceptibility, perceived severity, perceived benefit, perceived barrier, and self efficacy helps to take action on the prevention of anemia. This study aimed to analyze the correlation of knowledge, the Health Belief Model, and consumption patterns with anemic status at Saint Stanislaus High School. This study used a cross-sectional design. The population in this study were all female students in grade X and XI of Saint Stanislaus Senior High School, totaling 84 people. The cluster random sampling technique was used to calculate the total amount of samples, totaling 46 people as the sample of this study. The data collected included respondent characteristics, knowledge rate, construction of Health Belief Model, consumption patterns of iron source foods differentiated into levels of adequacy and frequency of eating, and anemia status. The results of this study showed that 14 of the respondents aged 16 years experienced anemia (30.43%). The correlation of knowledge and the incidence of anemia significantly correlated, with a p-value of 0.044 (p <0.005). Meanwhile, constructs of the Health Belief Model and the level of adequacy of food consumption of iron sources had no correlation with the incidence of anemia (p> 0.005). The frequency of kale consumption as a source of non heme iron had a correlation with the incidence of anemia (p <0.005). This study concluded that there was a correlation with knowledge and the incidence of anemia in Saint Stanislaus High School students. Proper nutrition education based on the concept of the Health Belief Model can be given to students to let them have an understanding, good attitude, and practice prevention measures for anemia well. Keywords: knowledge, Health Belief Model, iron consumption pattern, anemic